1999
DOI: 10.1002/(sici)1096-8628(19991029)86:5<439::aid-ajmg9>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Perlman syndrome: Four additional cases and review

Abstract: Perlman syndrome was first described in 1973 and comprises nephromegaly with renal dysplasia and Wilms tumor, macrosomia, cryptorchidism, and multiple facial anomalies. Polyhydramnios and hypoglycaemia are often found. Twelve children have been described from six different families. Five came from one family whose Yemenite Jewish parents were second cousins. Autosomal recessive inheritance has been suggested. Prognosis is severe with neonatal death in most children. We report on 4 new cases of Perlman syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Some cases with inadequate clinical detail but who had a sib presenting with documented Perlman syndrome were included [Perlman et al, 1975; Greenberg et al, 1986; Chitty et al, 1998]. Two sibs have been published twice [van der Stege et al, 1998; Henneveld et al, 1999]. We did not include three reports in the present review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases with inadequate clinical detail but who had a sib presenting with documented Perlman syndrome were included [Perlman et al, 1975; Greenberg et al, 1986; Chitty et al, 1998]. Two sibs have been published twice [van der Stege et al, 1998; Henneveld et al, 1999]. We did not include three reports in the present review.…”
Section: Discussionmentioning
confidence: 99%
“…Neri et al 1984 further delineated the syndrome in two affected sibs and proposed the name Perlman syndrome. Additional patients have been described by Greenberg et al 1986, Hamel et al 1989, Chernos et al 1990, Grundy et al 1992, Herman and McAlister 1995, Coppin et al 1997, Fahmy et al 1998, Henneveld et al 1999, Schilke et al 2000, Piccione et al 2005 and Pirgon et al 2006. Some cases have been described with prenatal sonographic findings [Chitty et al, 1998; van der Stege et al, 1998; DeRoche et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…We presented our 1st case to Dr Max Perlman, who originally described the syndrome later given his name [5,7], and he did not feel that the facial dysmorphology of this infant was consistent with PS (personal communication, May 2004). Due to the partial overlap of the phenotypes of BWS and PS and reports of chromosome 11 alterations in PS, it has been suggested that the 2 syndromes represent differential involvement of genes within the 11p15 region [8]; however, this contention has been refuted [9]. In addition to BWS and PS, we found no evidence of other causes of ascites with fetal hydrops, such as metabolic storage disease, or gastrointestinal or cardiac disorders [7].…”
Section: Discussionmentioning
confidence: 48%
“…Perlman syndrome and Sotos syndrome are two overgrowth syndromes that have been associated with congenital hyperinsulinism [1,18]. The mechanisms of hypoglycaemia in syndromic HI with gigantism remain unclear.…”
Section: Perlman Syndrome and Sotos Syndromementioning
confidence: 99%